Therapeutic Monitoring of Vancomycin Implemented by Eremomycin ELISA - Inna A. Galvidis; Yury A. Surovoy; Vitaly R. Sharipov; Pavel D. Sobolev; Maksim A. Burkin (Antibiotics)
Background/Objectives: Due to a narrow therapeutic window, side-effects, toxicities, and individual pharmacokinetics (PK) variability, WHO classifies vancomycin (VCM) as a “watch antibiotic” whose use should be monitored to improve clinical effectiveness. Availability and ease of use have made the immunoassay technique the basic tool for the therapeutic drug monitoring (TDM) of VCM concentrations. Methods: The present study describes the development of a TDM tool for VCM based on anti-eremomycin (ERM) antibody enzyme-linked immunosorbent assay (ELISA). Results: The optimized assay format based on coating a BSA-VCM conjugate allowed for the equal recognition of both VCM and ERM (100 and 104%) and was not influenced by concomitant antibiotics. Among the sample pretreatments studied, acetonitrile deproteinization was preferred to effectively remove the most likely matrix interferences and to provide 75–96% VCM recovery in the range of 3–30 mg/L, ensuring reliable determination of the key PK parameter, Ctrough. Higher peak concentrations were measured in more diluted samples. Several inflammatory indices, biochemical markers, and key proteins significantly different from normal in critically ill patients were investigated as assay interferers and were found not to interfere with VCM analysis. Serum samples (n = 108) from patients (n = 4) with extensive burn injuries treated with combined antibiotic therapy were analyzed for VCM using the developed assay and confirmed by LC-MS/MS, demonstrating good agreement. Conclusions: The approach used shows that the same analytical instrument is suitable for measuring structurally related analytes and is fully adequate for their therapeutic monitoring. Suboptimal exposure based on Ctrough values obtained with standard dosing regimens supports the use of TDM in these patients.